False positive complement fixation tests with respiratory virus preparations in bird fanciers with allergic alveolitis. Issue 5 (October 1977) - Taylor, A J; Taylor, P; Bryant, D H; Longbottom, J L; Pepys, J
Abstract : False positive raised complement fixation titres to egg-grown virus preparations were found in six pigeon fanciers suffering from extrinsic allergic alveolitis but not in six similar budgerigar fanciers. The raised titres in the pigeon fanciers fell fourfold over a short interval in the absence of avian exposure and were attributable to antibodies directed against antigens from hen's egg in which the test virus preparations were grown. Such antigens were shown to be present in the virus preparations. In view of the clinical similarities between influenza and acute extrinsic allergic alveolitis, it is essential that a diagnosis of influenza in bird fanciers is not based on either a single raised titre or a fourfold fall in complement fixation titre without appropriate control tests with avian antigens.